Difference in apical and basal growth of the frontal bone primordium in Foxc1ch/ch mice. (August 2014) - Machida, Akihiko; Okuhara, Shigeru; Harada, Kiyoshi; Iseki, Sachiko
Abstract The frontal and parietal bones form the major part of the calvarium and their primordia appear at the basolateral region of the head and grow apically. A spontaneous loss of Foxc1 function mutant mouse, congenital hydrocephalus (Foxc1ch/ch), results in congenital hydrocephalus accompanied by defects in the apical part of the skull vault. We found that during the initiation stage of apical growth of the frontal bone primordium in the Foxc1ch/ch mouse, the Runx2 expression domain extended only to the basal side and bone sialoprotein (Bsp) and N‐cadherin expression domains appeared only in the basal region. Fluorescent dye (DiI) labeling of the frontal primordium by ex‐utero surgery confirmed that apical extension of the frontal bone primordium of the mouse was severely retarded, while extension to the basal side underneath the brain was largely unaffected. Consistent with this observation, decreased cell proliferation activity was seen at the apical tip but not the basal tip of the frontal bone primordium as determined by double detection of Runx2 transcripts and BrdU incorporation. Furthermore, expression of the osteogenic‐related genes Bmp4 and‐7 was observed only in the basal part of the meninges during the initiation period of primordium growth. These results suggest that a loss of Foxc1 function affects skull bone formation of the apical region and that Bmp expression in the meninges might influence the growth of the calvarial bone primordium.